Rancang Bangun Sistem Informasi Pemesanan Online Aktivitas Wisata (anexplore.id) - Santana, Febriana; Nirmala, Bagus Putu Wahyu; Dewi, Eka Grana Aristyana (Universitas Pendidikan Ganesha, 2021)
Bali is one of the main tourist destinations in Indonesia. The island of Bali which is known to be known almost all over the world is one of the most favorite destinations. The large number of domestic and foreign tourists who come to Bali make the tourism industry in Bali grow rapidly. Most of the livelihoods of Balinese people are also in the tourism industry.The existence of a commission system in the world of tourism provides an opportunity for everyone to earn additional income by inviting them to do tourism activities. These opportunities have a positive impact on the wider community in generating additional income without having to leave their main job. To facilitate ordering tourism activities, this research has developed an information system for ordering tourism activities at Anexplore.id. In addition, this research also discusses the distribution of commissions for those registered as freelance agents. The programming language used in this research is PHP using the Agile method as the system foundation. This research succeeded in developing an information system for ordering tourism activities in a bold manner, with the results of testing the functionality of the system using black box testing. It can be said that the system built can run well.